2011
DOI: 10.5007/2175-7925.2011v24n4p39
|View full text |Cite
|
Sign up to set email alerts
|

<b>Flora vascular de um inselbergue no estado da Paraíba, Nordeste do Brasil</b><br>DOI:10.5007/2175-7925.2011v24n4p39

Abstract: Este trabalho caracterizou a composição fl orística de um inselbergue no município de Puxinanã, estado da Paraíba, Nordeste do Brasil. Foram registradas 97 espécies distribuídas em 35 famílias. Asteraceae (12 spp.), Euphorbiaceae e Fabaceae (nove spp. cada), Rubiaceae e Convolvulaceae (oito spp. cada) foram as cinco famílias melhor representadas em número de espécies, englobando 47,42% do total das registradas. O hábito herbáceo foi o predominante estando presente em 39% das espécies. Em seguida, sobressaíram-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
(23 reference statements)
2
6
2
2
Order By: Relevance
“…The genus Pilosocereus is also well represented in surveys of Brazil's semiarid region (Zappi et al 2016), and is often represented by P. pachycladus in environments with mean annual rainfall over 500 mm (Silva et al 2010;Pereira Júnior et al 2012) or by P. gounellei in environments with mean annual rainfall lower than 500 mm (Oliveira et al 2009;Santos et al 2009;Santos & Melo 2010;Tölke et al 2011) or by both species, as was the case in the present study.…”
Section: Discussionsupporting
confidence: 51%
“…The genus Pilosocereus is also well represented in surveys of Brazil's semiarid region (Zappi et al 2016), and is often represented by P. pachycladus in environments with mean annual rainfall over 500 mm (Silva et al 2010;Pereira Júnior et al 2012) or by P. gounellei in environments with mean annual rainfall lower than 500 mm (Oliveira et al 2009;Santos et al 2009;Santos & Melo 2010;Tölke et al 2011) or by both species, as was the case in the present study.…”
Section: Discussionsupporting
confidence: 51%
“…The taxonomic richness seen in this study was greater than that found on other rock outcrops in the Brazilian Northeast, which presented a number of climbing species ranging from five to 27 (França et al 2005, 2006, Neves and Conceição 2007, Araújo et al 2008, Porto et al 2008, Gomes and Alves 2009, Gomes et al 2011, Tölke et al 2011, Gomes and Leite 2013, Lucena et al 2015. It is worth noting that these studies did not have climbing plants as their main focus, a factor that may have influenced the sampling effort and consequently the documented richness of the different areas, in addition to differences in geographic size and preservation status between areas.…”
Section: Discussioncontrasting
confidence: 56%
“…Despite this, works conducted by Pitrez (2006), Porto et al (2008) and Tölke et al (2011), in addition to this study, reflect this family's representativeness in the State's rocky outcrops. Of the 10 species of Bromeliaceae recorded in the study area, seven were found in Pocinhos and six in Puxinanã; being the species Orthophytum disjunctum L.B.…”
Section: Resultsmentioning
confidence: 91%
“…Both cities are identified, from a geomorphologic point of view, as part of the Borborema Plateau (AESA 2014). Pocinhos (07º0514'S -36º0356'W) and Puxinanã (07º08'62.1S,35º58'31.4W) are located at a varying altitude of 600 to 700 m. Pocinhos with annual maximum temperature of 30 ºC and minimum of 21 ºC, and highest precipitation period in March and June (Andrade et al 2007) and Puxinanã with maximum registered temperature of 28 ºC and minimum of 16 ºC, with precipitation periods from January, March to July, and August (Tölke et al 2011).…”
Section: Methodsmentioning
confidence: 99%